PENGGEMBALAAN MGR. W. SCHOEMAKER DALAM MENGHADIRKAN GEREJA KEUSKUPAN PURWOKERTO DI TENGAH MASYARKAT - Stefanus Heriyanto (Jurnal Teologi (Journal of Theology), 2012)
The spreadof the Churchin differentparts of the worldled toareal challenge, namelyhow to develop a Church thattrulyrootedin the local culture. This challenge is alsofaced by the Diocese of Purwokerto. One ofthe most influentialfigures who made the Diocese of Purwokerto incorporated in the local culture isMonseigneur W.Schoemaker. Thus, understanding his life as amissionary priest in Purwokerto and his pastoral services as the Apostolic Vicar of Purwokerto and then as the first bishop in the Diocese of Purwokerto is very important. This research focuses on exploring three points: 1) life history of W.Schoemaker before his ordination as a missionary priest;2) his concern in serving ruralpeople as a missionary priest; 3) and his policy as a bishop of the Diocese of Purwokerto in developing the Diocese of Purwokertos identity as a local Church.